Mock Oral Board Examinations via Web‐based Video Teleconferencing in the Era of COVID‐19. Issue 1 (24th September 2020) - Chhabra, Neeraj; Winfield, Ashlea; Dyer, Sean; Hedayati, Tarlan
Abstract: Owing to infection control measures necessitated by the COVID‐19 pandemic, many educational didactic components within residency programs have needed to adapt to virtual formats. We describe and evaluate the transition of an in‐person mock oral board certification examination to an entirely virtual format. Oral board cases consisting of two single cases and one triple case were adapted to a virtual format using a Web‐based video teleconferencing platform. Faculty examiners underwent 20‐minute training sessions prior to the examination. Both resident examinees and faculty examiners completed postexamination surveys. The system usability scale (SUS) was used to assess the usability of the new format by the faculty examiners. Fifteen resident examinees completed the mock virtual oral board examination with eight faculty examiners. All faculty members completed the postexamination survey. The mean (±SD) SUS score was 90.6 (±11.5) out of a maximum of 100. Eleven of 15 (73%) resident examinees completed the postexamination survey. All respondents agreed or strongly agreed that examiner instructions were easy to understand and that examiners were adept at using the Web‐based platform. Some technical issues were encountered including audio difficulties for some examiners. Respondents were split regarding personal preference for virtual or in‐person mock oral board formats. Utilizing video teleconferencing software to provide a virtual, Web‐based alternative to in‐person mock oral board examination was feasible, and the virtual format was shown to have high usability despite minimal training time for experienced faculty examiners.